2002
DOI: 10.1002/1099-0690(200206)2002:11<1727::aid-ejoc1727>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Eur. J. Org. Chem. 11/2002

Abstract: The cover picture shows a branched poly(proline) peptide whose synthesis has successfully been achieved using a combination of step-wise and convergent solid-phase peptide methodology. Aminoproline was used as a branching unit in order to maintain structural coherence with the rest of the sequence, although other trifunctional amino acids were also tested. Assembly of different units of this peptide could lead to poly(proline) dendrimers. These new biocompatible architectures may have interesting applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These molecules showed in vitro capacity to cross the eukaryotic cell membrane and moderate cytotoxicity, thus opening up their use as drug delivery systems 11. However, the rigidity of the polyproline branches hampered the synthesis, mainly as a result of the highly compact core space, which was translated into low yield and purity 8a8c…”
Section: Introductionmentioning
confidence: 99%
“…These molecules showed in vitro capacity to cross the eukaryotic cell membrane and moderate cytotoxicity, thus opening up their use as drug delivery systems 11. However, the rigidity of the polyproline branches hampered the synthesis, mainly as a result of the highly compact core space, which was translated into low yield and purity 8a8c…”
Section: Introductionmentioning
confidence: 99%
“…20 This is due to the presence of pendant carboxylated aliphatic chain in the polymer structure, creating large polymeric cavities in the nanostructure for the effective preservation of various cargos. In addition, other amino acid-based biopolymers, such as polyglutamic acid, 21 poly(aspartic acid) 22 and polyproline dendrimers, 23 are also widely used in biomedical applications due to their enhanced solubility, biocompatibility and low profile cytotoxicity. Syntheses of such biomacromolecules involve polymerization of an appropriate cyclic monomer 22 or selective -NH 2 group protection and deprotection of the corresponding amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of branched polyproline peptides is not at all straightforward. After a careful study of several different approaches, we have chosen the optimized synthetic route shown in Scheme .
2 Building Block Solid-Phase Synthesis
…”
Section: Resultsmentioning
confidence: 99%